On variational problems of the theory of potential - Zoriy , N. V. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
A series of variational problems are formulated and investigated on classes of charges, associated with space condensers. Solvability statements are established and the properties of the investigated extremal quantities are studied.